Wheat Resistance to Stripe and Leaf Rusts Conferred by Introgression of Slow Rusting Resistance Genes - Reda Ibrahim Omara; Atef Abdelfattah Shahin; Shaimaa Mahmoud Ahmed; Yasser Sabry Mostafa; Saad Abdulrahman Alamri; Mohamed Hashem; Mohsen Mohamed Elsharkawy (Journal of Fungi, 2021)
Twenty-three wheat genotypes were evaluated for stripe and leaf rusts, caused by Puccinia striiformis f. sp. tritici and Puccinia triticina f. sp. tritici, respectively, at seedling and adult stages under greenhouses and field conditions during the 2019/2020 and 2020/2021 growing seasons. The race analysis revealed that 250E254 and TTTST races for stripe and leaf rusts, respectively were the most aggressive. Eight wheat genotypes (Misr-3, Misr-4, Giza-171, Gemmeiza-12, Lr34/Yr18, Lr37/Yr17, Lr46/Yr29, and Lr67/Yr46) were resistant to stripe and leaf rusts at seedling and adult stages. This result was confirmed by identifying the resistance genes: Lr34/Yr18, Lr37/Yr17, Lr46/Yr29, and Lr67/Yr46 in these genotypes showing their role in the resistance. Sids-14 and Shandweel-1 genotypes were susceptible to stripe and leaf rusts. Twelve crosses between the two new susceptible wheat genotypes and the three slow rusting genes (Lr34/Yr18, Lr37/Yr17, and Lr67/Yr46) were conducted. The frequency distribution of disease severity (%) in F2 plants of the twelve crosses was ranged from 0 to 80%. Resistant F2 plants were selected and the resistance genes were detected. This study is important for introducing new active resistance genes into the breeding programs and preserving diversity among recently released wheat genotypes.